2018
DOI: 10.1093/jac/dky145
|View full text |Cite
|
Sign up to set email alerts
|

Obesity following ART initiation is common and influenced by both traditional and HIV-/ART-specific risk factors

Abstract: Obesity following ART initiation is frequent among HIV-infected adults. Key risk factors include female sex, HIV disease severity and INSTI use. Further research regarding the association between INSTIs and the development of obesity is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
124
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(149 citation statements)
references
References 29 publications
(31 reference statements)
21
124
1
3
Order By: Relevance
“…INSTI‐based ART regimens are now the recommended first‐line treatment for most PWH [12], but several recent studies, primarily from single sites or cohorts, report greater weight gain among persons receiving INSTI‐based ART regimens for initial therapy as compared to protease inhibitor (PI) and non‐nucleoside reverse transcriptase inhibitor (NNRTI)‐based regimens. In a cohort from Brazil, PWH receiving RAL‐based regimens were sevenfold more likely to become obese (BMI ≥ 30kg/m 2 ) compared to those receiving NNRTI‐ or PI‐based regimens [13]. In other observational studies, INSTI‐based regimens generally, and particularly DTG‐based ART regimens [14‐17], were also associated with greater weight gain.…”
Section: Introductionmentioning
confidence: 99%
“…INSTI‐based ART regimens are now the recommended first‐line treatment for most PWH [12], but several recent studies, primarily from single sites or cohorts, report greater weight gain among persons receiving INSTI‐based ART regimens for initial therapy as compared to protease inhibitor (PI) and non‐nucleoside reverse transcriptase inhibitor (NNRTI)‐based regimens. In a cohort from Brazil, PWH receiving RAL‐based regimens were sevenfold more likely to become obese (BMI ≥ 30kg/m 2 ) compared to those receiving NNRTI‐ or PI‐based regimens [13]. In other observational studies, INSTI‐based regimens generally, and particularly DTG‐based ART regimens [14‐17], were also associated with greater weight gain.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly women had greater VAT gain on raltegravir vs PI than men, and black vs nonblack individuals [8]. The association between dolutegravir or raltegravir vs elvitegravir use and weight gain was confirmed in observational cohorts of PLWH initiated with ART [9,10,11]. Weight gain following ART initiation could be attributable in part to a "return to health" phenomenon, but is also clearly associated with individual INSTI and with personal factors as sex and ethnicity [12].…”
Section: Role Of Instimentioning
confidence: 99%
“…Several studies have reported an increasing prevalence of being overweight and obese in PWH, and have demonstrated that weight gain occurs in many PWH after initiating antiretroviral therapy (ART) [1][2][3][4]. Factors associated with weight gain in PWH include demographic factors (such as sex and race), HIV disease-related factors (such as disease stage and viral load), and ART-associated factors (specific antiretroviral drugs) [2,3,[5][6][7][8][9]. These observations have led to several non-exclusive mechanistic hypotheses for ART-associated weight gain, including a mirroring of societal trends, a return-to-health effect of ART, improved tolerability of ART regimens, and off-target effects of antiretroviral drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Among the antiretroviral drugs, the integrase strand transfer inhibitors (INSTIs) have specifically been associated with weight gain in studies of treatment-naïve PWH and in PWH switching to INSTI-based therapy [2,7,8,10]. Whether this association is causative is unknown, and no mechanism to explain the association has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%